Mapping the Location and Infrastructure of Slum Settlement Areas in Palembang City Using Mobile-Based GIS - Rahman, Satrio; Irwansyah (Jurnal Teknologi Informatika dan Komputer, 2025)
Slum settlements are one of the problems that the government in Indonesia needs to pay more attention to, one of which is the city of Palembang. To manage slum settlements, the first thing that needs to be considered is the infrastructure. Because infrastructure is the first step to support the smooth activities of the surrounding community. This can be seen if the infrastructure does not meet the requirements, such as the physical condition seen from the buildings which are very close together with low construction quality, the roads are damaged and have potholes, the public sanitation and drainage are not functioning as well as the large amount of rubbish which is not managed properly. This could all happen due to government limitations in the monitoring and checking process. To make it easier for the community and government, the author developed an Application for Mapping Locations and Infrastructure of Slum Settlement Areas in Palembang City Using Mobile-Based GIS. GIS is an organized collection of computer hardware, software, geographic data and personnel designed to efficiently acquire, store, update and display all forms of geographically referenced information. In this research, the research methodology used is the Extreme Programming method. In making this application the author used a mobile programming base as a system development application. Research results show that this application can make it easier for the public to make complaints regarding slum conditions and help the government monitor and handle problems more effectively.